Absence of renal phenotype in hereditary haemorrhagic telangiectasia. Issue 10 (4th October 2018) - Healy, Lachlan; Nicholls, Kathleen; Gibson, Robert; Stella, Damien; Bogwitz, Michael; Taylor, Jessica; Walsh, Maie; Donaldson, Liz; Winship, Ingrid
Abstract: Hereditary haemorrhagic telangiectasia is characterised by abnormal blood vessel formation, producing telangiectasia and arteriovenous malformations in multiple organs. Information regarding possible renal involvement in hereditary haemorrhagic telangiectasia is limited. This study assessed renal structure and function in 11 patients with genetically confirmed diagnosis and known arteriovenous malformations in lung, liver, gastrointestinal tract or brain. All had significant current or past epistaxis. Despite the vascularity of the kidneys, we found no evidence of renal involvement. This observation warrants further consideration.